Perioperative effects of caudal block on pediatric patients in laparoscopic upper urinary tract surgery: a randomized controlled trial - Bingdong Tao; Kun Liu; Dandan Wang; Mengmeng Ding; Ni Yang; Ping Zhao (BMC, 2019)
Abstract Background While caudal block has been widely used during pediatric lower limbs and lower abdominal surgeries, few studies to date have evaluated the perioperative effects of caudal block on pediatric patients in laparoscopic upper urinary tract surgery. Methods Ninety-six pediatric patients, aged 6 months to 7 years, ASA grade I-II, scheduled to undergo laparoscopic upper urinary tract surgery, were randomized to a non-block group (no caudal block performed), an ROP1.0 group (patients received 1.0 mL/kg of 0.15% ropivacaine) and an ROP1.3 group (patients received 1.3 mL/kg of 0.15% ropivacaine). The primary outcome variable was perioperative fentanyl use. The secondary outcome variables were pain score, hemodynamic fluctuation, the number of patients needing rescue fentanyl and side effects. Results Caudal block with 1.3 mL/kg of 0.15% ropivacaine significantly decreased perioperative fentanyl usage (ROP 1.3 vs. non-caudal block, P < 0.01; ROP 1.3 vs. ROP 1.0, P < 0.05). Moreover, patients in the ROP1.3 group, compared to those without, displayed more stable hemodynamics, lower pain score in the PACU and 8 h after operation, less demand for rescue fentanyl, shorter time of PACU stay. Conclusions Caudal block with 1.3 mL/kg of 0.15% ropivacaine reduced perioperative fentanyl use during laparoscopic upper urinary tract surgery on pediatric patients and produced good postoperative analgesia when compared with no caudal block and caudal block with 1.0 mL/kg of 0.15% ropivacaine. Trial registration Clinical trial number: ChiCTR1800015549, chictr.org.cn.